Palanka in the 1644-1646 Sijjil of Tuzla - Dostović, Nihad (Historical Thought, 2024)
This paper analyses five documents from the Sijjil of the Tuzla qadi/judge from 1644–1646, where the term “palanka” is mentioned. All documents are firmans, or decrees issued in the name of the Sultan from the Divan of Buda. Two firmans deal with cerāḫors, a construction workers from the privileged re‘aya class who worked on fortress repairs. Two firmans address the usurpation of the duty of reciting prayers for the Sultan – du’āgūluḳ. One firman pertains to wandering groups of Roma. In all documents, “palanka” is a general term; no specific place is directly referred to as “palanka,” nor are any further characteristics provided. These documents are significant for historical studies as they highlight strong connections between Ottoman Hungary and Ottoman Bosnia through various situations.